Molecular and biological characterization of apium virus Y infecting parsley in Brazil - Ribeiro-Junior, Marcos Roberto [UNESP]; Gorayeb, Eduardo Silva [UNESP]; Nogueira, Angélica Maria [UNESP]; Cruciol, Giovana Carolina Dourado [UNESP]; Nascimento, Daniele Maria [UNESP]; Pavan, Marcelo Agenor [UNESP]; Krause-Sakate, Renate [UNESP] (Springer Nature, 2021)
Parsley is a biannual herbaceous plant, frequently used as a condiment in Brazilian gastronomy, also having medicinal properties. This work reports the molecular identification, partial host range, and complete genome sequencing of an apium virus Y (Potyvirus) isolate (ApVY-Br) infecting parsley in Brazil. Complete genome sequencing revealed a 9913nt long virus with high identity with previously reported ApVY isolates. The isolate was capable of infecting parsley, coriander, Chenopodium amaranticolor, and Chenopodium quinoa plants. Bayesian phylogenetic analyses based on the complete genome and coat protein sequences clustered the ApVY isolates based on sampling locations.
Keywords: ApVY; Petroselinum crispum; Potyvirus